La Belgique calomnié : réponse à M. P.-J. Proudhon - Boniface, Joseph; Defré, Louis-Joseph (Bruxelles : Tircher, 1862)
Bibliotheek Camille Huysmans
Frans
Brochure
Keywords: politieke geschiedenis; België